COMPENSATION, MOTIVATION, PERFORMANCE AND WORK SPIRITUALITY OF LECTURERS: A STRATEGY MODEL FOR DEVELOPING HIGHER EDUCATION RESOURCES IN INDONESIA - Sazly, Syukron; Tambunan, Diana; Harun, Muhamad; Saputra, Suwanda Aditya (Universitas Muhammadiyah Tangerang, 2024)
Employee performance is one of the most important factor to achieve an organization objectives. Employee performance is a measurement the ability of employees to carry out their taks and obligations well and with high satisfaction. This research aims to develop theoretical modeling on how to measure and research related to employee performance, especially lecturers at tertiary institutions in Indonesia. The theory we used is based on the theory put forward by Colquitt which explains the Integrative Model of Organizational Behavior. The research method is qualitative with literature study, theoretically analyzing theories from 30 previous researchers which have been published in Scopus indexed international journals and also accredited national journals. The result shows, compensation and motivation factors have a positive and significant influence on employee performance and also the work spirituality factor as a moderating variable which also determines the level of this influence. Recommendations to future researchers to examine several factors other than compensation and motivation that influence employee performance, both as predictor variables and moderating variables.